TRANSFORMATIVE LEARNING THROUGH DISORIENTING DILEMMAS AND CRITICAL REFLECTION IN A MOVIE THE RON CLARK STORY - Siahaan, Safnidar; Eriyanti, Ribut Wahyu; Asih, Ria Arista (Universitas Islam Sumatera Utara (UISU), 2024)
This research investigates transformative learning theory using the biographical film The Ron Clark Story, which depicts an innovative teacher's experiences in an inner-city school. Jack Mezirow defines transformative learning theory as using jarring situations and critical reflection to catalyze dramatic perspective shifts. The study seeks to bridge the gap between academic concepts and their practical applications in educational contexts. The film was analyzed using a qualitative content analysis method, which included systematic data collecting and triangulation of primary and secondary sources. The findings highlight important unsettling challenges confronting Ron Clark, such as culture differences and student resistance, prompting critical reflection and transformative learning. Clark changes his teaching skills through reflective practices, incorporating culturally relevant methods such as rap in the classroom and making personal sacrifices to help his kids. This strategy creates a transformed classroom atmosphere, improving both teaching methods and student outcomes. The study indicates that The Ron Clark Story exemplifies the transforming impact of critical reflection in education. It emphasizes the value of resilience and adaptability in teaching and offers practical advice for educators looking to apply transformative learning practices. This study adds to the discussion about transformative learning by providing a tangible example of theoretical principles put into practice, with the goal of informing professional development programs and improving educational results.